Optimization of PT. Ciomas Adisatwa Distribution Routes to Minimize The Distribution Cost - Cendy N. Ardiansyah; Dwi Sukma D (Tibuana, 2022)
Optimal distribution means that the process of sending goods from the company to agents has a basis for scheduling and determining routes appropriately, and products received by consumers are in good and fresh condition in accordance with the specified time with low operating costs. PT Ciomas Adisatwa is one of the Japfa group companies that produces processed chicken products that are fresh, hygienic, and of good quality but have a problem with the route that is passed in the distribution process. Based on the knowledge of the driver and assistant the distance traveled is uncertain which results in a long delivery time. The distribution costs become expensive and erratic. The purpose of this study is to determine the optimal distance from each branch outlet and provide suggestions for route improvements to get the lower cost using the dynamic programming method. The Dynamic Program method provides distance savings of 1.0261 Km and cost savings of Rp. 1,426,433, with a percentage of cost savings of 4.7%, so that the Dynamic Program can be used for company distribution.